Differential target multiplexed spinal cord stimulator: a review of preclinical/clinical data and hardware advancement. - Murphy, Melissa Z; Fishman, Michael A (Pain Management, 2023)
Spinal cord stimulation (SCS) is an effective neuromodulation technique for treating chronic neuropathic pain. Recent rapid growth in understanding its mechanism has led to the development of glial cell-based differential target multiplexed (DTM) stimulation and its derivative algorithm. Both preclinical research and clinical trials in humans showed superior pain relief using DTM SCS compared with traditional SCS. Another multicenter prospective clinical trial showed significant pain score reduction and energy saving using the DTM derivative algorithm. This review paper summarizes the evidence related to using DTM stimulation for other painful conditions such as nonsurgical low back pain and upper-limb pain. All these advanced programming options can be delivered using an innovative platform, the Medtronic Intellis™ neurostimulator.